MTBVAC induces superior antibody titers and IgG avidity compared to BCG vaccination in non-human primates - Marco Polo Peralta-Álvarez; Keya Downward; Andrew White; Hugo Redondo Azema; Laura Sibley; Charlotte Sarfas; Alexandra Morrison; Mike Dennis; Delia Diaz-Santana; Stephanie A. Harris; Shuailin Li; Eugenia Puentes; et al. (npj Vaccines)
Abstract The only currently licensed vaccine against tuberculosis (TB), Bacille Calmette Guérin (BCG), is insufficient to control the epidemic. MTBVAC is a live attenuated strain of Mycobacterium tuberculosis (M.tb) and is one the most advanced TB vaccine candidates in the pipeline. It is more efficacious than BCG in preclinical models including non-human primates (NHPs), and has demonstrated safety and immunogenicity in human populations. To better understand the immune mechanisms underlying the superior efficacy conferred by MTBVAC, we characterized M.tb-specific antibody responses in NHPs vaccinated with either BCG or MTBVAC. MTBVAC vaccination induced higher titers of IgG, IgM and IgA, and higher avidity IgG compared with BCG vaccination. IgG avidity correlated with protection following M.tb challenge in the same animals, validating the association previously reported between this measure and protection in the context of intravenous BCG vaccination, suggesting that IgG avidity may represent a relevant marker or correlate of protection from TB.